1986
DOI: 10.1152/ajpcell.1986.250.3.c468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forskolin and cyclic nucleotides on isometric force in rat aorta

Abstract: The present study was undertaken to determine the extent to which cyclic nucleotide-induced relaxation in the intact rat aorta is mediated at the level of the contractile system. The relaxant effects of the cyclic nucleotide analogues [8-bromoguanosine 3',5'-cyclic monophosphate (8-BrcGMP) and dibutyryladenosine 3',5'-cyclic monophosphate (DBcAMP)] and forskolin were examined in both the intact vessel and a Triton X-100-skinned preparation of rat thoracic aorta. Relaxation of a norepinephrine-induced contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The affinity of MLCK for the Ca2+-calmodulin complex has been reported to decrease when it is phosphorylated by cyclic AMP-dependent protein kinase, resulting in inhibition of MLCK activity (Conti & Adelstein, 1981). Others have reported that cyclic AMP-dependent protein kinase has little direct effect on MLCK activity in vascular smooth muscle (Gerthoffer, Trevethick & Murphy, 1984;McMahon & Paul, 1986). The relationship between [Ca2+]i and MLC phosphorylation does not change with increasing compared to decreasing [Ca2+]i, i.e.…”
Section: Discussionmentioning
confidence: 90%
“…The affinity of MLCK for the Ca2+-calmodulin complex has been reported to decrease when it is phosphorylated by cyclic AMP-dependent protein kinase, resulting in inhibition of MLCK activity (Conti & Adelstein, 1981). Others have reported that cyclic AMP-dependent protein kinase has little direct effect on MLCK activity in vascular smooth muscle (Gerthoffer, Trevethick & Murphy, 1984;McMahon & Paul, 1986). The relationship between [Ca2+]i and MLC phosphorylation does not change with increasing compared to decreasing [Ca2+]i, i.e.…”
Section: Discussionmentioning
confidence: 90%
“…where 1.06 g/cm 3 was used as an estimate of tissue density [20]. This approach yields values for vessel thickness that are similar to thickness measurements determined by morphometry [21].…”
Section: Methodsmentioning
confidence: 93%
“…At the end of the experiment, rings were cut open longitudinally and the muscle dimensions (segment length and circumference) were measured with a calibrated optical micrometer [20]. The tissue was then gently blotted and weighed (wet weight).…”
Section: Methodsmentioning
confidence: 99%
“…In intact SM, this would cause a rise in intracellular cAMP; but the problem of how low Po2 may stimulate cAMP production in skinned SM remains. It was established 400 Ca" RESPONSIVENESS OF MYOFILAMENTS IN HYPOXIA 401 (McMahon & Paul, 1986) that adenylate cyclase, which is located predominantly on plasma membrane, retains its activity in skinned SM, because the adenylate cyclase stimulant forskolin induces noticeable (17-4+1 5 %) relaxation in skinned SM. Additionally, it is known that a guanine nucleotide-binding protein (G protein) has been implicated in the transduction of signal from several types of receptors and regulates adenylate cyclase activity.…”
Section: Discussionmentioning
confidence: 99%